Synthesis and Characterization of Bent-Core Liquid Crystal/Modified γ-Al2O3 Nanocomposites - Karabuga, Hande; Mert, Hatice Hande; Karanlik, Gurkan; Ocak, Hale (WILEY-V C H VERLAG GMBH, 2019)
A new bent-core liquid crystal (LC) compound CPDB derived from a 4-chlororesorcinol central core unit with two terephthalate based rod-like units carrying chiral (S)-3,7-dimethyloctyloxy terminal chains has been synthesized and LC / modified gamma-Al2O3 nanocomposites have been prepared in different compositions. The effects of being doped with 0.3, 0.5, 1.0, 2.0, 3.0 and 4.0% modified gamma-Al2O3 nanoparticles on mesomorphic properties of the new bent-core liquid crystal, which shows an enantiotropic SmA phase, were investigated by differential scanning calorimetry and optical polarizing microscopy. The surface of gamma-Al2O3 nanoparticles was modified with a cationic agent, cetyltrimethyl ammonium bromide (CTAB), used as a compatibilizer for providing interaction of liquid crystal molecule with alumina nanoparticles. The immobilization of CTAB on gamma-Al2O3 nanoparticle surface via physical adsorption in solution was confirmed by TGA and preserved of crystalline structure of aluminium oxide was proved by XRD analysis. The presence and homogeneous distribution of alumina nanoparticles in LC were confirmed by using Scanning Electron Microscopy (SEM) and energy dispersive X-ray (EDX) spectroscopy. The modified gamma-Al2O3 nanoparticles in CPDB liquid crystal give rise to a slight increase in the mesomorphic range by preserving mesophase type as observed in pure liquid crystalline compound.
Keywords: Liquid crystals; Mesomorphic properties; Nanocomposites; Nanoparticles; BANANA-SHAPED MESOGENS; ELECTROOPTICAL PROPERTIES; LATERAL SUBSTITUENTS; MESOPHASE BEHAVIOR; CARBON-MONOXIDE; POLAR ORDER; CRYSTALS; CHIRALITY; NANO; Chemistry